PENGEMBANGAN MEDIA PEMBELAJARAN MYSTEQUEST UNTUK MENINGKATKAN HASIL BELAJAR SISWA DI SEKOLAH DASAR - Botutihe, Sahria Putri; Abdullah, Gamar; Arif, Rifda Mardian; Isnanto, Isnanto; Nurfadliah, Nurfadliah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The aim of this research is to develop Mystequest learning media that meets the criteria for feasibility, practicality and effectiveness in science and science learning in order to improve student learning outcomes on Metamorphosis of Living Creatures material in class III at SDN No. 62 Kota Timur. This research is a research method (Research and Development) using the ADDIE development research model, which includes the stages of analysis, design, development, Implement, and Evaluate. Based on validation results from experts and users, Mystequest media obtained an average score of 96.25%, which is considered very suitable for use by teachers and students in elementary schools. To test practicality, researchers used teacher observation sheets, which showed a total score of 47 out of a maximum score of 48, thus reaching an average of 97.91% which is considered very practical. In the aspect of effectiveness, the application of media in class III of SDN No. 62 Kota Timur was measured through pretest and posttest. As a result, the total pretest score was 31.88 which increased to 81.88 in the posttest. The N-Gain calculation shows a score of 0.72, which is in the “medium” category. In conclusion, Mystequest media effectively improves student learning outcomes and is suitable for use in elementary schools.